2017
DOI: 10.1039/c7dt01372h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted one-pot synthesis of new ionic iridium complexes of [Ir(bzq)2(N^N)]+A type and their selected electroluminescent properties

Abstract: Iridium C,N-cyclometalated complexes with an ionic structure are considered to be promising candidates for application in host/guest solid-state phosphorescent single-layer devices because the employment of such dopants offers the possibility of reducing their concentration in organic matrices as well as allows obtaining organic light emitting devices (OLEDs) with interesting emission parameters. We report herein a methodology enabling the synthesis of cyclometalated ionic iridium(iii) complexes of the type [I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…The reaction scheme for the synthesis of the Ir(III) complex is presented in Scheme 1, which involves in a revision of the synthetic procedure previously reported by Orwat and coworkers. 38 Briey, a microwave pressure reactor was used in a one-pot synthetic method for the complex formation. Reaction time and temperature were optimized for the synthesis of the Ir(III) complex based on the starting materials including a mixture of IrCl 3 $3H 2 O and the three ligands in basic medium.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The reaction scheme for the synthesis of the Ir(III) complex is presented in Scheme 1, which involves in a revision of the synthetic procedure previously reported by Orwat and coworkers. 38 Briey, a microwave pressure reactor was used in a one-pot synthetic method for the complex formation. Reaction time and temperature were optimized for the synthesis of the Ir(III) complex based on the starting materials including a mixture of IrCl 3 $3H 2 O and the three ligands in basic medium.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Vibrational analyses for the optimized structures of isolated molecules were performed to verify if a given structure corresponded to potential energy minima and to calculate zero-point vibrational energies, entropies, and thermal corrections for Gibbs free energies. Solvent-solute interactions were taken into account with the aid of the polarizable continuum model (PCM) [75][76][77] and acetonitrile or dichloromethane as the solvent usually used in experimental studies [78,79]. All calculations were carried out with Gaussian09 software package [80] in PL-Grid infrastructure.…”
Section: Computational Details and Theorymentioning
confidence: 99%
“…Results from numerous literature reports indicated that frontier molecular orbitals analysis constitutes a useful proxy for experimentally recorded photophysical properties of iridium(III) complexes [78,79,[82][83][84]. It is known that frontier molecular orbitals (FMO) of complex ground state S 0 are related to its spectral properties [86].…”
Section: Frontier Molecular Orbitals Analysismentioning
confidence: 99%
“…Moreover, the EL spectrum is red shifted in comparison to the PL spectra. Such behavior is very common and is connected with the formation of different excited states in PL and EL [51]. In PL, the excited states are created by the light, and are localized on one molecule.…”
Section: Oled Characterizationmentioning
confidence: 99%